(untitled) (Proceedings of the International Conference on Public Health, 2021)
Hospital Information System must provide innovative services in digitals era. The interoperability systems made data interconnected between hospitals, health services and the ministry of health. This system is urgently needed to improve National health services. The aim of the study to assess the preparation, barriers and benefit of interoperability system implementation. The study was a systematic review of journal articles by assessing several databases, from Pubmed, Proquest, EBSCO, and Springer Link to identify relevant studies with PRISMA. The keyword is “Health Information Interoperability, Hospital and Implementation”. Ten articles were obtained which matched the inclusion and exclusion criteria. These articles explained how the system can be applied, from the preparation of the infrastructure, such as the standard systems that have been adopted, Fast Healthcare Interoperability Resources (FHIR) from Health Level 7 (HL7). The barriers were the standardized data between hospitals with same vendors, so the hospitals were reluctant to implement it. The benefit was the hospital services improve quality in accuracy, legibility, completeness and consistency of documents. Hoped that interoperability can make health information systems more effective by preventing repeated examinations and so that can reduce health costs. This system is a big challenge throughout the world, the role of government and policymakers is needed in implementation.